Cloud observability in action - Hausenblas, Michael (Manning Publications Co., 2024)
Cloud native systems are made up of hundreds of moving parts. When something goes wrong, it's not enough to know there is a problem-- you need to know where it is, what it is, and how to fix it. This book takes you beyond traditional monitoring, explaining observability systems that turn application telemetry into actionable insights. Cloud observability in action gives you the background and techniques you need to successfully introduce observability into cloud-based serverless and Kubernetes environments. In it, you'll learn to use open standards and tools like Open-Telemetry, Prometheus, and Grafana to build your own observability system and end reliance on proprietary software. You'll discover insights from different telemetry signals, including logs, metrics, traces, and profiles. Plus, the book's rigorous cost-benefit analysis ensures you're getting a real return on your observability investment
Includes index
Keywords: Cloud computing; Observers (Control theory); Infonuagique; Observabilité (Théorie de la commande)